Oral cancer detection through WhatsApp: the importance of teleconsultation during the COVID-19 pandemic - Pareja, Giovanna Nogueira; Melo, Gabriela Banacu de; Oliveira, Jhosepher Previati de; Kaba, Shajadi Carlos Pardo; Braz-Silva, Paulo Henrique; Gallo, Camila de Barros (Journal of Oral Diagnosis, 2021)
Introduction: The COVID-19 pandemic has changed the routine of dental care all over the world due to the high risk of contamination by handling body fluids and aerosol production. Biosafety measures were intensified, and dental appointments were restricted to emergencies. In Oral Medicine, the early diagnosis of oral cancer is one of the main urgencies. Objective: The aim of this article is to report a case of oral cancer that was diagnosed during social isolation through a digital messaging platform, in a patient with history of oral potentially malignant disorder. Case Report: The present case report refers to the diagnosis of oral squamous cell carcinoma in an 83-year-old Asian woman with a history of oral potentially malignant disorder. The aforementioned malignant lesion was suspected during a remote consultation using the WhatsApp platform. After the telephone consultation regarding the possible diagnosis, the patient sought care at the referral hospital and underwent clinical examinations, laboratory testing, computed tomography scans and an incisional biopsy to confirm the diagnosis and begin with adequate treatment. Conclusion: The need to mitigate the spread of SARS-CoV-2 prompted the need for and implementation of Teledentistry resources in all fields, including Oral Medicine. Despite being rare, malignant lesions can be diagnosed, as was done in the present report and Oral Medicine plays a crucial role in early diagnosis.